1998
DOI: 10.1007/s004140050177
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA extraction and typing from isolated dentin-experimental evaluation in a Korean population

Abstract: This study reports mtDNA polymorphisms in both hypervariable segments HV1 and HV2 of the non coding D-loop region from 60 unrelated Koreans. In contrast to two previous Korean data base studies, mtDNA was extracted separately from pulp tissue and root dentin of teeth obtained from dentists. Dentin turned out to be a reliable source of mitochondrial DNA. This can be of practical importance in forensic identification case work after a long post-mortem interval since pulp decomposes rapidly. The extraction method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 13 publications
4
46
0
Order By: Relevance
“…The three sequences with this motif that appear in the Korean data of Snäll et al (2002), however, tested positively for the RFLP site +4830 HaeII (recognizing a transition at nt 4833) of haplogroup G. We additionally found the 4833 transition (confirmed by +4831 HhaI) in four mtDNAs from China (Table 2). Because all of these mtDNA sequences that belong to haplogroup G have (near-)matches with sequences sampled in Japan (Horai et al 1996;Imaizumi et al 2002;Koyama et al 2002), Korea (Pfeiffer et al 1998;Lee et al 1997Lee et al , 2002, and China (Tsai et al 2001;Yao et al 2000Yao et al , 2003a, it appears that these sequences also belong to haplogroup G. The vast majority of these HVS-I and HVS-II sequences share the 150 polymorphism. In particular, eleven HVS-I and HVS-II sequences from the Korean sample of Lee et al (1997) carry the partial motif 16223-16325; seven of them have the additional part 16362-150 of the motif, Yao et al (2003a) and the data underlying figure 1 of Mishmar et al (2003), respectively; 2 n.d. = not determined.…”
Section: Distinguishing Asian From Native American Mtdnasmentioning
confidence: 77%
“…The three sequences with this motif that appear in the Korean data of Snäll et al (2002), however, tested positively for the RFLP site +4830 HaeII (recognizing a transition at nt 4833) of haplogroup G. We additionally found the 4833 transition (confirmed by +4831 HhaI) in four mtDNAs from China (Table 2). Because all of these mtDNA sequences that belong to haplogroup G have (near-)matches with sequences sampled in Japan (Horai et al 1996;Imaizumi et al 2002;Koyama et al 2002), Korea (Pfeiffer et al 1998;Lee et al 1997Lee et al , 2002, and China (Tsai et al 2001;Yao et al 2000Yao et al , 2003a, it appears that these sequences also belong to haplogroup G. The vast majority of these HVS-I and HVS-II sequences share the 150 polymorphism. In particular, eleven HVS-I and HVS-II sequences from the Korean sample of Lee et al (1997) carry the partial motif 16223-16325; seven of them have the additional part 16362-150 of the motif, Yao et al (2003a) and the data underlying figure 1 of Mishmar et al (2003), respectively; 2 n.d. = not determined.…”
Section: Distinguishing Asian From Native American Mtdnasmentioning
confidence: 77%
“…The internal node is shared by Croats, Mongols and Turkicspeaking Uighurs, Kazakhs, Turks and even by one South Asian (Sri Lankan, our unpublished results) mtDNA. A further extension of this bough via additional transitions at nps 16129 and 16344 leads to a twig, shared by Korean and Japanese 13,14,18 populations, including Ainus and Ryukyu people. Yet another twig (np 16172) is occupied by mtDNAs, found among Koreans and Turkic-speaking Uighurs.…”
Section: Resultsmentioning
confidence: 99%
“…5 and 77 in [27]; however, resequencing revealed that in either case C317G was a phantom mutation. C320G was scored once in [63], where the rCRS nucleotide was, however, mistyped as T. The raw data of sample no. 36 at this position are highly inconclusive, and the position should have been assigned with an N.…”
Section: Phantom Mutations In Hvs-iimentioning
confidence: 99%